PENGARUH VERBAL ABUSE ORANG TUA TERHADAP PERILAKU SOSIAL USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Putri Ramadhanny; Zulkifli Zulkifli; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to know the influence of abuse that is done by the old age of the behavior of 5-6 years in TK Negeri Pembina 1 Pekanbaru. The samples in this study numbered 31 parents and children. The method used in this study is a quantitative correlation to see the relationship between the free variables by binding. The data collection techniques used are by observation and poll. Data analysis techniques using the Pearson Product moment correlation test with the IBM SPSS for Windows Ver. 25.0 program. From the research results known social behavior levels of children are in a category suffi with a percentage value of 63.87% and the verbal rate of abuse of parents is in medium category with a percentage value of 68.28%. Based on the hypothesis test results obtained there is a negative and significant relationship between verbal abuse of parents with the behavior of the children aged 5-6 years in TK Negeri Pembina 1Pekanbaru. This can be noted from the value of the correlation coefficient of 0.547 and the value of the coefficient of determination resulting from 29.9% has the meaning that verbal abuse 29.9 affects the social behavior of the child. Key Words : Social behavior, Verbal abuse